Las MiPymes y su Incidencia en la Generación de Empleo en el Perú: Periodo 2005-2014 - Basurco Valcarcel, Ana Cla (2016)
This way MSMEs are not part of a uniform set of production units yet some strategies to stimulate its growth are not equally effective when created without considering their particularities. This research on MSMEs and their impact on job creation in Peru during 2005 - 2014 has the main purpose to determine MSMEs and their impact on employment generation period: 2005 - 2014. On the other hand, we will identify formal MSMEs not only in the study period as business stratum, regions and economic activity, but also their impact on the specified period. We will also identify how MSMEs contribute to employment generation through the PEA by size enterprise, economic activity and employment segment and finally, describe the factors which limit the creation and development of MSMEs in Peru. In order to develop this research, we have used the descriptive technical method and apply this research is library research, on the other hand we have techniques for processing and analysis of information that are as follows: documentary analysis, tabulation tables with numbers and percentages, making graphics, literature review; and techniques for processing data then appoint: Sorting and classification, computer processing using computers, as we have the research design of a box. As a possible answer to the problem, this following hypothesis has been formulated: MSMEs have had a significant impact on job creation in Peru period 2005 - 2014. Having developed this research and the results obtained are evaluated concluded that MSMEs have a positive impact on employment generation in Peru , an increase of 1,278,076 new jobs and an annual average of 127,806 jobs representing 1.6% of the annual average. However, there are still certain barriers to the development of these enterprises, which do not allow the increase of its participation in the business stratum.